Does Local Environmental Governance Improve Tourism Companies' Performance? Evidence from Vietnam. (April 2022) - Nguyen, Bach
Institutions (rules of law) are important to tourism activities. However, national institutions cannot become effective when the execution of rules of law is inconsistent at the local levels. This study thus examines the role of local governance arrangements on the performance of tourism companies, focusing on environmental governance quality. Utilizing institutional theory, we propose a U-shaped relationship between tourism performance and environmental governance. When environmental governance arrangements are initially implemented, the performance of local tourism companies may be negatively affected due to institutional conflicts. However, as new environmentally responsible values are gradually institutionalized, the performance of the local tourism sector will improve. Analyzing more than three thousand tourism companies in Vietnam in 2018 using instrumental variable technique to control for endogeneity, we find some evidence to support the U-shaped function. Also, it is found that the U-shaped effect is stronger on foreign inbound tourists than on domestic tourists.